Molecular mechanisms of endomembrane trafficking in plants. Issue 1 (22nd September 2021) - Aniento, Fernando; Sánchez de Medina Hernández, Víctor; Dagdas, Yasin; Rojas-Pierce, Marcela; Russinova, Eugenia
Abstract: Endomembrane trafficking is essential for all eukaryotic cells. The best-characterized membrane trafficking organelles include the endoplasmic reticulum (ER), Golgi apparatus, early and recycling endosomes, multivesicular body, or late endosome, lysosome/vacuole, and plasma membrane. Although historically plants have given rise to cell biology, our understanding of membrane trafficking has mainly been shaped by the much more studied mammalian and yeast models. Whereas organelles and major protein families that regulate endomembrane trafficking are largely conserved across all eukaryotes, exciting variations are emerging from advances in plant cell biology research. In this review, we summarize the current state of knowledge on plant endomembrane trafficking, with a focus on four distinct trafficking pathways: ER-to-Golgi transport, endocytosis, trans-Golgi network-to-vacuole transport, and autophagy. We acknowledge the conservation and commonalities in the trafficking machinery across species, with emphasis on diversity and plant-specific features. Understanding the function of organelles and the trafficking machinery currently nonexistent in well-known model organisms will provide great opportunities to acquire new insights into the fundamental cellular process of membrane trafficking. Abstract : We summarize the current knowledge on plant endomembrane trafficking with a focus on ER-to-Golgi transport, endocytosis, trans-Golgi network-to-vacuole transport and autophagy.